Changes in Gut Microbiota by the Lactobacillus casei Anchoring the K88 Fimbrial Protein Prevented Newborn Piglets From Clinical Diarrhea - Qin, Da; Bai, Yongfei; Li, Yan; Huang, Yanmei; Li, Liyang; Wang, Guihua; Qu, Yi; Wang, Jiabin; Yu, Li-Yun; Hou, Xilin (Frontiers in Cellular and Infection Microbiology, 2022)
In the last 20 years, accumulating evidence indicates that the gut microbiota contribute to the development, maturation and regulation of the host immune system and mediates host anti-pathogen defenses. Lactobacillus casei (L.casei) is a normal flora of the gastrointestinal tract in mammals, and as a great mucosal delivery vehicle have widely used in bioengineering. However, a prevention diarrhea role of commensal intestinal microbiota interfered by the recombinant L.casei (rL.casei) in new born piglets is not well-understood. In our study, new born piglets were orally fed with the rL.casei surface-displayed the fimbrial protein K88 of enterotoxigenic Escherichia coli (ETEC) and their feces were collected for a period of time after feeding. The next generation sequencing of these fecal samples showed that the relative abundance of L.casei was significantly increased. The oral administration of the rL.casei altered the intestinal microbial community as evidenced by altered microbial diversity, microbial taxonomic composition. Remarkably, the functional enhancing of the intestinal bacterial community by the rL.casei was positively correlated with membrane transport, and replication and repair (p<0.05). The specific antibody detection indicates that high levels of anti-K88 secretory immunoglobulin A (sIgA) were induced in fecal samples and systemic immunoglobulin G was produced in serum. Thus, oral administration of the rL.casei not only activated the mucosal and humoral immune responses in vivo, but also contributed to shape the intestinal probiotics in newborn piglets and to decrease diarrhea in piglets caused by ETEC k88 about 24%.